Prevalence of symptoms suggestive of sleep apnea among children and its impact on academic performance - Silvia D. Boyajian; Muna A. Salameh; Kholoud Alzyoud; Enas A. Amaireh; Lujayn Badah; Malek Al Qutami; Mira Alsharayri; Osama Abubaker; Rzan Shwashreh (Journal of the Egyptian Public Health Association)
Abstract Background Obstructive sleep apnea (OSA) is a common condition in pediatrics that requires prompt recognition and management to minimize its negative impact on their health and development. Data on the prevalence of OSA among school-age minors in Jordan is scarce. This study aims to estimate the prevalence of OSA in children and adolescents and identify factors that make them more likely to have OSA and its impact on academic achievement. Methods This school‐based cross‐sectional study was conducted from January to March 2023. A questionnaire including information on demographic variables, school performance, and a validated sleep-related breathing disorder (SRBD) scale for pediatrics was distributed to 1798 students in schools all over Amman. The prevalence of OSA (defined as SRBD score > 33%) was reported as a proportion along with its 95% confidence interval. Results Out of the 2000 questionnaires distributed, 1798 were analyzed. Among these, 1079 (60%) were from children aged 5 to 10 years, and 719 (40%) were from adolescents aged 11 to 18 years. The prevalence of high risk for OSA (HR-OSA) was higher among adolescents than in children (25.6% vs. 20.8%). Adolescents with unemployed fathers were more likely to be HR-OSA (33.70 vs 17.57%, p < 0.001). In contrast, paternal employment did not affect the prevalence of HR-OSA in children. Sleep talking, bruxism, and sweating during sleep were more common among children with positive SRBD. Nocturnal enuresis (NE) was associated with positive SRBD in children and adolescents. HR-OSA was associated with poor academic performance in both study groups. Conclusion HR-OSA is highly prevalent in Jordanian children and adolescents. HR-OSA can occur alongside other sleep disorders, and it significantly impairs the academic performance of affected individuals. This study found an association between high risk for OSA and other sleeping disorders (sleep talking, sleep bruxism, and sweat during sleeping) and nocturnal enuresis which needs to be confirmed in larger studies.